Increased delta aminolevulinic acid and decreased pineal melatonin production. A common event in acute porphyria studies in the rat. - Puy, H (1996)
Tryptophan (TRP) is the precursor of melatonin, the primary secretory product of the pineal gland. Hepatic heme deficiency decreases the activity of liver tryptophan pyrrolase, leading to increased plasma TRP and serotonin. As a paradox, patients with attacks of acute intermittent porphyria (AIP), exhibit low nocturnal plasma melatonin levels. This study using a rat experimental model was designed to produce a pattern of TRP and melatonin production similar to that in AIP patients. Pineal melatonin production was measured in response to: (a) a heme synthesis inhibitor, succinylacetone, (b) a heme precursor, delta-aminolevulinic acid (Ala), (c) a structural analogue of Ala, gamma-aminobutyric acid. Studies were performed in intact rats, perifused pineal glands, and pinealocyte cultures. Ala, succinylacetone, and gamma-aminobutyric acid significantly decreased plasma melatonin levels independently of blood TRP concentration. In the pineal gland, the key enzyme activities of melatonin synthesis were unchanged for hydroxyindole-O-methyltransferase and decreased for N-acetyltransferase. Our results strongly suggest that Ala overproduced by the liver acts by mimicking the effect of gamma-aminobutyric acid on pineal melatonin in AIP. They also support the view that Ala acts as a toxic element in the pathophysiology of AIP.